Uso de prótese expansora auxiliando na reabilitação com prótese ocular - Iyda, Bruno Garib [UNESP] (2014)
Treatment with ocular prosthesis plays an important role in preservation of facial esthetics, and properly stimulate the tissue growth. However, the ideal is that the prosthesis is adapted as soon as the problem is installed, minimizing sequelae and disturbances during the orbital growth. The purpose of this case report is to describe the rehabilitation of the eyeball of a two months old pacient, emphasizing indications and limitations. Clinical case: Patient, 2 months old, female was referred to College of Dentistry of Araçatuba (FOA / UNESP) for an eyeball rehabilitation. During the physical and clinical examinations, the pacient was diagnosed with an absence of the eyeball due to domestic trauma, which caused eyelid collapse and facial deformity. The treatment plan proposed was the manufacture of an expander prosthesis and posteriorly, the rehabilitation with ocular prosthesis. The expander prosthesis was made of acrylic resin and remained in the patient's anophthalmic socket for 60 days in order to return the volume needed. After this period an ocular prosthesis was made of N1 and colorless acrylic resin; artificial iris was obtained by painting a cardboard disk with oil paint. After the treatment, it can be seen that Expander prosthesis provided the increase of the anophthalmic cavity and promoted the patient's adaptation in relation to the occurred situation. The Ocular prosthesis set the aesthetic balance of the face which will eventually reflect positively on psychological and social development of the child